The Development of Video-Based Guidance and Counseling Media on Self-Love - Heriyanti Savitri Oddang; Abdul Saman; Ahmad Yasser Mansyur; Muhammad Anas (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2022)
This study aims to determine (1) the need to develop a video-based guidance and counseling media on self-love for adolescents in Public Junior High School 21 Makassar (SMP N 21 Makassar) (2) a prototype of video guidance media about self-love for adolescents, and (3) the validity of the video-based guidance and counseling media on self-love for adolescents for students of SMP N 21 Makassar. This study is a research and development implementing Borg and Gall research model. A questionnaire, interviews, and scales were used to collect the data. The results of the research show that (1) video-based guidance and counseling media on self-love for adolescents is media needed by school counselors in SMP N 21 Makassar, (2) the video-based guidance and counseling media on self-love is developed in the form of audio-visual animation, and (3) the video-based guidance and counseling media on self-love developed to increase students' self-esteem is valid after meeting the criteria in feasibility testing, accuracy testing, and utility testing